Festskrift til Mogens Herman Hansen: Polis & Politics. Studies in Ancient Greek History, eds. P. Flensted-Jensen, T.H. Nielsen, L. Rubinstein. Museum Tusculanums Forlag 2000. 656 sider - Flensted-Jensen, Pernille (AIGIS, 2024)
Intet.